(untitled) (Research, Society and Development, 2023)
Currently, within the wide range of alternative therapies to drugs for Alzheimer’s disease (AD), music therapy stands out for promoting the preservation of not only socialization skills, but also expression, in addition to helping in cases of behavioral disorders, such as depression and anxiety. In this sense, the main objective of this work is the elaboration of a literature review that aims both at identifying and understanding the effects of music therapy in patients diagnosed with AD. This was done using the PICO strategy (acromion for Patient, Intervention, Comparison and Outcome) and defining the following clinical question as a guide for the entire study: “Music therapy is an effective non-pharmacological therapeutic resource in the treatment of patients with Alzheimer’s disease?". In addition, in order to answer this question, a bibliographic survey was carried out through electronic searches in the following databases: Scientif Electronic Library Online (SciELO), National Library of Medicine (PubMed), EbscoHost, Google Scholar and Regional Medicine Library (BIREME), being used, after the selection stage, 23 articles for the construction of the literary review. In general, based on the results found, it was possible to conclude that the use of music therapy as an alternative treatment in cases of dementia, such as AD, in addition to promoting an intense structural and connective modification of the brain, is capable of delaying cognitive decline and improve behavioral symptoms, functional status and, consequently, the quality of life of patients affected by this pathology.